PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERAWATAN KAKI PENCEGAHAN ULKUS DIABETIK DI WILAYAH KERJA PUSKESMAS SENTOSA BARU KOTA MEDAN - Andriyani, Syafitri; Silaen, Harsudianto (Excellent Midwifery Journal, 2024)
Foot care is an action carried out by individuals both in conditions of normal blood sugar levels and elevated blood sugar levels which is carried out regularly to maintain personal hygiene, especially the feet. Diabetic ulcers can cause disability or death if prevention is not carried out in patients with type 2 DM. In patients with diabetes mellitus, sufferers often experience disorders or wounds on the feet consisting of thickening of the skin and nail tissue, minor wounds or serious injuries such as gangrene (wounds). which is rotting or expanding). And one of the preventive efforts for type 2 DM patients is to provide health education about foot care to reduce the occurrence of complications from diabetic foot ulcers using leaflets. The aim of the research is to determine the effect of health education on foot care to prevent diabetic ulcers in the working area of ​​the New Seontosa Health Center in Medan City. This research uses a pre-experimental design and uses pretest and posttest design methods. Sampling used proportional sampling with a total sample of 65 respondents. The research instrument used was a diabetic foot care questionnaire to prevent ulcers. The data analysis used was the Wilcoxon test. The results of the research show that there is an influence of health education on foot care to prevent diabetic ulcers in the work area of ​​the Sentosa Baru Health Center, Medan. The Wilcoxon statistical test shows a p - value <0.05. So it can be concluded that there is an influence of health education on foot care to prevent diabetic ulcers in the work area of ​​the Sentosa Baru Health Center, Medan.